Alkali-Aggregate reaction in Western Cape concrete - Mahomed, Zubair Lall (Department of Civil Engineering, 2019)
Alkali-aggregate reaction, AAR, was first discovered in 1938 by Stanton in the USA. Subsequently, researchers across the globe have reported incidences of the reaction with different aggregates in their respective countries. The reaction entails the interaction between reactive silica found in aggregates and alkali in the pore solution of concrete. Through research, the reaction has been categorised into three main classes depending on the type of aggregate used. Alkali-silica reaction, ASR, being one of those classes, is the most common one and is the primary concern in the local concrete industry in the Western Cape, where reactive greywacke aggregates are used. In South Africa, the problem has often been dealt with using low alkali cement. However, those low alkali resources have been depleted and more alkali-rich resources are now being used in the production of cement. This completes the three requirements needed for ASR reaction to occur, namely a high alkali source, presence of reactive silica and moisture conditions. Furthermore, the introduction of greywacke crusher sand as a partial substitute to natural sands in local concrete mixes, implies that more reactive silica is available in the mixes. The research aims at finding whether the current concrete mixes are prone to alkali silica reaction and how to mitigate this expansion using cement extenders, which is the most common ASR mitigation measure. The long-term performance test, which allows testing of concrete, generally takes a minimum of 6-12 months to complete. As such, attention was turned towards the use of an accelerated mortar bar test (AMBT), which is generally used as an indicator test in the preliminary stages of the testing. However, the AMBT test imposes material limitations such as cement type and aggregate grading. Consequently, modifications were made to the AMBT test to allow for the concurrent use of reactive fine aggregates and coarse aggregate as well as a commercial cement. The first stage of this project involved the use of a modified AAR-2 AMBT test and was subdivided into three phases. Phase A was centred around investigating the use of reactive fine aggregates and reactive coarse aggregates in conjunction. For this purpose, 40% of the total aggregate blend by mass was constituted of a sand blend having both reactive (greywacke) and non-reactive (Philippi dune sand) components, while the remaining aggregate portion was a 9.5 mm greywacke coarse aggregate. The reactive fine aggregate level was varied in the sand blend and the ASR expansion recorded. A limited pessimum effect was observed at around 40-60% reactive greywacke by mass in the sand blend, whereby the expansion recorded peaked. Phase B of Stage 1 then involved the use of a 50/50 greywacke crusher sand/Philippi dune sand in the sand blend as a base mix. Cement extenders were then substituted in different levels for the cement. For this work, common replacement levels of 20, 30 and 40 percent fly ash and 40, 50 and 60 percent corex slag were used. It was found that all the mixes mitigated the ASR expansion to acceptable levels, that is below the 0.10% expansion, while increasing cement extender levels reduced the expansion further. It was also found that fly ash was more effective at reducing ASR than corex slag. Phase C of Stage 1 involved identifying the mechanisms behind which cement extenders mitigate ASR. Subsequently, the mixes used in Phase B were replicated with the exception that an inert limestone filler, “Kulubrite 10”, was used instead of the reactive cement extenders. It was observed that the limestone filler does reduce the expansion but to a much lesser extent than the reactive cement extenders. This implied that the cement extenders not only dilute the alkali content but also undergo further reaction which removes more alkali from the pore solution. The second stage of the project dealt with the influence of ASR gel formation on compressive strength. Compressive strength tests were performed on 2 sets of cubes for each mix, which were exposed to different curing conditions, namely a water bath at 22-25 ̊C and an alkaline solution of 1M NaOH at 80 ̊C. It was observed that there is reduction in strength as the expansion increases. Scanning electron microscopy, SEM, performed in Stage 3, of the samples confirmed that this phenomenon is due to the increased number of cracks as the expansion increases. Other subsidiary tests conducted in Stage 3, such as light microscopy and EDS, resulted in inconclusive results and need to be further investigated. Lastly, Stage 3 involved conducting long-term testing using a modified version of the AAR-4 test and field performance test. Five ‘real-life’ concrete mixes, based on the mixes in Stage 1, were cast and are still under observation. The initial measurements on the AAR-4 samples showed no sign of expansion as of 15 weeks of testing. This was thought to be due to the un-boosted alkali content of the cement, 0.7 % Na2O eq, which may have not been enough to start the reaction. The preliminary results of the field testing at 15 weeks of age showed that apparent shrinkage was occurring, likely due to the environmental influences over this period (summer months). This could be attributed to the fact that the ASR gel formation mechanism is still in its early stages in those specimens or has not started yet. The final results of these tests, at 6 months and 2 years respectively, are however needed to confirm whether the modifications made in Stage 1 of this research resulted in a good approximation of what is to be expected from the use of reactive greywacke fine and coarse aggregates in conjunction. In general, it can be concluded that the concurrent use of reactive greywacke crusher sand and reactive greywacke coarse aggregate in concrete mixes, would not be deleterious to structures. Nevertheless, it is advised that a minimum of 20% fly ash or 40% ground granulated corex slag by mass of the total binder content is used, as per the current conventional precautions.